The Comparison of Biomechanic Alteration on Cervical Angle During Walking with And Without Smartphone Dual-Task Texting Among Smartphone Users - Susilo, Taufik Eko; Hasbi Al Farizy, Muhammad; Wijianto; Tri Sudaryanto, Wahyu; Wahyuni; Fitriyah, Qonitah Faizatul; Fatmarizka, Tiara (Physiotherapy Health Science (PhysioHS), 2024)
Background: The prevalence of smartphone usage continues to rise, becoming deeply embedded in daily routines across all age groups. Young adults are particularly significant users, often engaging in dual-tasking, such as texting while walking. This behavior may lead to biomechanical alterations, particularly in cervical posture, which could have long-term musculoskeletal implications. Objective: This study investigates the biomechanical alterations in cervical angle during walking with and without dual-task texting among smartphone users, specifically focusing on young adults. Method: A quantitative observational study was conducted using a single group repeated measurement design. Thirty male participants, aged 21.07 ± 1.05 years, were involved. Cervical angle degrees were measured using video analysis, with data processed through the Kinovea application to extract kinematic coordinates. Results: The One Way Repeated ANOVA Test revealed a significant increase (p<0.01) in cervical angle degree during texting while walking, indicating that dual-tasking notably affects cervical posture. Conclusion: The findings highlight that dual-task texting induces significant biomechanical changes in cervical posture.